Preparation method of nano silicon dioxide / fluorocarbon resin durable super-hydrophobic composite coating and application of nano silicon dioxide / fluorocarbon resin durable super-hydrophobic composite coating on wind turbine blade

Through the two-step spraying method of nano-silicon dioxide/fluorocarbon resin, a durable super-hydrophobic composite coating of nano-silicon dioxide/fluorocarbon resin is formed, which solves the ice-proof and mechanical wear resistance of wind turbine blades in high humidity and cold environments. Problem, efficient ice protection and durability improvement have been achieved.

CN119119812AInactive Publication Date: 2024-12-13CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411268530.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing superhydrophobic composite coating has reduced anti-icing effect in high humidity and cold environments, and the mechanical wear resistance and durability are insufficient, making it difficult to process large-area on wind turbine blades.

Method used

Using the two-step spraying method of nano-silicon dioxide/fluorocarbon resin, the weather-resistant fluorocarbon resin is first sprayed as the bonding layer, and the surface layer is formed by spraying γ-GPTMS modified SiO2 nanoparticles, and the nanoparticles are self-precipitated and assembled. Technology, the hybrid state of inorganic particles-organic resin is formed, which imparts the coating roughness and low surface energy, and achieves the transition from hydrophobicity to superhydrophobicity.

Benefits of technology

It significantly extends the icing delay time of the droplets, reduces the ice bonding force and ice covering amount, improves the wear resistance and durability of the coating, and is suitable for large-area applications of wind turbine blades.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119812A_ABST
    Figure CN119119812A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coating materials, and discloses a preparation method of a nano silicon dioxide / fluorocarbon resin durable super-hydrophobic composite coating and application of the nano silicon dioxide / fluorocarbon resin durable super-hydrophobic composite coating on a wind turbine blade. The adhesive force of the coating on the base material is enhanced; in the second step, an inorganic particle-organic resin hybrid state is formed by spraying a super-hydrophobic modified SiO2 dispersion liquid and combining a nano-particle self-settling assembly technology, required roughness and low surface energy are given to the coating, and conversion from hydrophobicity to super hydrophobicity is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coating materials, and in particular relates to a method for preparing a nano-silicon dioxide / fluorocarbon resin durable super-hydrophobic composite coating and its application on wind turbine blades. Background Art

[0002] At present, the wind power industry is booming, but wind turbines in high-humidity and cold areas often face icing problems in winter, which poses a severe challenge to the normal operation of wind farms. According to statistics, even a short-term icing event of 45 minutes may cause a loss of 18% to 31% of power generation; secondly, icing will cause uneven load distribution on the blades, which may easily lead to blade breakage; in addition, ice may be thrown off when the blades rotate, posing a safety hazard. Icing has become one of the key issues that need to be urgently solved for the safe and efficient operation of the wind power industry. At present, traditional anti-icing methods including mechanical or thermal deicing technology are not only easy to damage the surface structure, but also have the disadvantages of low efficiency, high energy consumption and high manufacturing cost. Therefore, it is urgent to develop a material that can achieve self-anti-icing and easy deicing characteristics in easy-to-ice areas, so as to achieve the anti-icing / deicing goals without additional energy consumption, equipment and manual operation. With the development of material surface engineering, anti-icing technology of coating hydrophobic / super-hydrophobic coating on easy-to-ice surfaces has become one of the hot research fields.

[0003] The use of low surface energy materials and surface roughness to construct super-hydrophobic coatings can help delay the freezing time of droplets and remove them from the surface in time, and reduce the adhesion between the ice layer and the blade surface. It is considered to be a promising anti-icing / de-icing method. Hong et al. first roughened the surface of alumina ceramics, and then modified the surface with polydimethylsiloxane (PDMS) to prepare a super-hydrophobic coating with a water contact angle of 176.39° and a rolling angle as low as 1°. At -8°C, the ice delay time reached 189s. Gu Guangcheng et al. used silicone rubber and hexamethyldisiloxane to prepare an elastic de-icing coating, which showed excellent hydrophobic properties and low ice adhesion strength (9.6kPa). In a real wind farm environment, the coating can significantly reduce the ice thickness of the blade to only 8% of the uncoated blade. Lei et al. used a spray method to prepare a super-hydrophobic coating based on SiO2 nanoparticles and room temperature vulcanized silicone rubber, with a water contact angle of 165.5±2.7° and a rolling angle of 5.3±2.4°. It exhibits excellent anti-icing performance at -4℃ and -8℃, but the anti-icing effect of the coating decreases at -12℃ and -16℃. Hu Qin et al. prepared a super-hydrophobic coating combining carbon nanotubes (MWCNTs) and super-hydrophobic SiC particles by self-assembly by precipitation method, achieving a static contact angle of 151°-162° and a rolling angle of 4.3°-7.6°. The coating still maintains stable super-hydrophobic performance after multiple wears, but after long-term icing and "icing-deicing" cycles, the durability of the coating still needs to be further improved. Xie et al. prepared a super-hydrophobic composite coating based on polydimethylsiloxane (PDMS) / silicon dioxide (SiO2) on the surface of magnesium alloy, with a water contact angle of 153°, but in a 20cm periodic wear test under a load of 100g and 240-grit sandpaper, the super-hydrophobicity was lost after only two cycles, indicating that the mechanical wear resistance of the coating needs to be optimized. Daneshmand et al. prepared a superhydrophobic coating with a contact angle of 160° by spraying stearic acid-modified aluminum oxide nanoparticles on a hydrophobic resin adhesive layer. The coating has excellent hydrophobicity and mechanical stability, but high temperature environment will cause stearic acid to decompose, affecting the durability of the coating. Although researchers have achieved many results in the field of anti-icing research on superhydrophobic composite coatings, there are still many challenges in the current anti-icing methods. Most superhydrophobic micro-nano composite surfaces have difficulty in achieving both superhydrophobicity and mechanical durability, and most existing preparation methods are not suitable for large-area processing on wind turbine blades. Many bottlenecks limit its application in engineering. Summary of the invention

[0004] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide a method for preparing a nano-silica / fluorocarbon resin durable super-hydrophobic composite coating and its application on wind turbine blades.

[0005] In order to achieve the above object, the present invention provides a method for preparing a nano-silicon dioxide / fluorocarbon resin durable super-hydrophobic composite coating, comprising the following steps:

[0006] (1) dispersing nano-silica particles in anhydrous butanol and subjecting them to ultrasonic treatment; mixing γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent with water, stirring to fully hydrolyze, and cooling to room temperature; mixing the silane coupling agent / water mixed solution and the nano-silica / butanol mixed solution evenly, and subjecting them to magnetic stirring in a water bath to obtain γ-GPTMS-modified SiO2 nanoparticles;

[0007] (2) preparing a main agent solution with a fluorocarbon resin and an isocyanate, preparing a diluent with butyl acetate and propylene glycol methacrylate, mixing the main agent solution and the diluent, stirring them magnetically in a beaker, vacuuming and degassing to obtain a composite coating film-forming material, spraying the composite coating film-forming material on the surface of a glass fiber reinforced epoxy resin board, and pre-curing the composite coating film-forming material to form a bottom bonding layer;

[0008] (3) A certain amount of γ-GPTMS-modified SiO2 nanoparticles was mixed with butanol to obtain a surface layer solution, which was evenly stirred and ultrasonically dispersed, and then evenly sprayed on the surface of the underlying bonding layer by a spray gun to form a surface layer. After curing, a nano-silica / fluorocarbon resin durable super-hydrophobic composite coating was obtained.

[0009] Preferably, in step (1), the mass content of the nano-silicon dioxide particles in anhydrous butanol is 0.004-0.03 g / mL.

[0010] Preferably, in step (1), the γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent and water are mixed in a ratio of 1:1-1:5.

[0011] Preferably, in step (1), magnetic stirring is performed in a water bath at 50-70° C. for 0.5-3 h.

[0012] Preferably, in step (2), the mass ratio of the fluorocarbon resin to the isocyanate in the main solvent is 20:1-10.

[0013] Preferably, in step (2), the mass concentration of butyl acetate in the diluent is 50-70%.

[0014] Preferably, in step (2), the main agent solution and the diluent are mixed in a mass ratio of 10:8-10:1.

[0015] Preferably, in step (2), pre-curing is carried out at 30-70°C.

[0016] Preferably, in step (3), the concentration of SiO2 in the surface layer solution is 2-30%.

[0017] The present invention adopts a two-step spraying method that can be used for large-area construction. In the first step, a weather-resistant fluorocarbon resin that is compatible with the epoxy resin material of the wind turbine blade is sprayed as a bonding layer to enhance the adhesion of the coating to the substrate. In the second step, a super-hydrophobic modified SiO2 dispersion is sprayed, and a nano-particle self-sedimentation assembly technology is combined to form an inorganic particle-organic resin hybrid state, thereby giving the coating the required roughness and low surface energy, thereby achieving a transition from hydrophobicity to super-hydrophobicity. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Surface SEM images of GPTMS-SiO2 coatings with different mass fractions;

[0019] Figure 2 This is the EDS element analysis result of SHP-GFRP-3# super hydrophobic coating;

[0020] Figure 3 The graphs of static contact angle and rolling angle of the composite coating surface as a function of the amount of super-hydrophobic nano-SiO2 particles added;

[0021] Figure 4 This is the static water drop delayed freezing characteristic diagram of different samples at -12℃;

[0022] Figure 5 It is the freezing delay time, cooling time and freezing time of the droplet;

[0023] Figure 6 The test results of static ice adhesion of different samples at -16℃ and -12℃;

[0024] Figure 7 The test results of static ice bonding strength of different samples at -16℃ and -12℃;

[0025] Figure 8 The effect of friction cycle on the contact angle and rolling angle of SHP-GFRP-3# superhydrophobic coating;

[0026] Fig. 9 The surface ice coverage of different samples at -6℃ with wind speed v=4m / s;

[0027] Fig.10 The surface ice coverage of different samples at -6℃ with wind speed v=8m / s;

[0028] Fig.11 The ice mass variation curves of different samples at different times under wind speed v = 4m / s and 8m / s;

[0029] Fig.12 The ice mass reduction rate curve of the composite coating surface at different times compared with the uncoated surface at wind speed v = 4m / s and 8m / s. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0031] The experimental substrate material was glass fiber reinforced epoxy resin board (GFRP) with a size of 100 mm × 100 mm × 10 mm, which was polished, cleaned, and dried before use.

[0032] The raw materials used in the experiment are: fluorocarbon resin (FEVE), Hunan Ben'an Yada New Materials Co., Ltd.; propylene glycol methacrylate (PMA), butyl acetate (BA), γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent (γ-GPTMS), anhydrous butanol, analytical grade, Shanghai MacLean Technology Co., Ltd.; isocyanate curing agent (N3390), Shanghai Kaiyin Chemical Co., Ltd.; 20nm spherical silica nanoparticles (SiO2), Zhejiang Lijie Chemical Co., Ltd.

[0033] 1g of nano-SiO2 particles were dispersed in 30ml of anhydrous butanol and ultrasonically treated for 5min. 5ml of silane coupling agent γ-GPTMS was mixed with 10ml of water, stirred to fully hydrolyze, and cooled to room temperature. The silane coupling agent / water mixed solution and the nano-silica / butanol mixed solution were mixed evenly, and magnetically stirred in a water bath at 60°C for 2h to obtain γ-GPTMS-modified SiO2 nanoparticles (GPTMS-SiO2). By grafting hydrophobic functional groups on the surface of SiO2, the hydroxyl content of the surface was reduced, thereby achieving a transformation from hydrophilic to hydrophobic. γ-GPTMS is used as a coupling agent, and its methoxyl group (-CH3O) reacts chemically with water to become a silanol (-Si-OH) functional group. The silanol functional group undergoes a dehydration condensation reaction with the silanol on the nano-silica to organicize the SiO2 hydroxyl group to enhance its dispersibility and compatibility in fluorine-based polymers. The modification process is shown in formula (1-2).

[0034]

[0035] The FEVE main agent and isocyanate curing agent were prepared into a main agent solution with a mass ratio of 100:13, and BA and PMA were prepared into a diluent with a mass ratio of 7:3. The main agent solution and the diluent were mixed with a mass ratio of 3:2, magnetically stirred in a beaker for 5 minutes, and vacuumed for 2-3 minutes to degas to obtain a composite coating film-forming material, which was sprayed on the surface of the GFPR substrate and pre-cured at 60°C to form a bottom bonding layer. A certain amount of GPTMS-SiO2 nanoparticles was mixed with butanol to obtain a surface layer solution with SiO2 concentrations of 4.76%, 6.25%, 9.09%, and 16.67%, respectively. After stirring and ultrasonically dispersing for 30 minutes, it was evenly sprayed on the surface of the pre-cured coating by a 0.3mm caliber spray gun at a pressure of 58PSI to form a surface layer. In order to obtain a uniform coating, the spray gun was placed vertically to the substrate at a distance of 15cm, and moved along the S-shaped spray route at a constant speed. Due to natural sedimentation under the action of gravity, the interfacial bonding force between the modified SiO2 and FEVE is enhanced and evenly distributed. After curing for 3 hours, super-hydrophobic SiO2 / FEVE composite coatings with SiO2 mass proportions of 14.63%, 18.37%, 24.66%, and 37.5% were obtained, named HP-GFRP-1#, HP-GFRP-2#, SHP-GFRP-3#, and HP-GFRP-4#, respectively. Among them, "HP" stands for hydrophobic and "SHP" stands for superhydrophobic. GFRP-0# means uncoated.

[0036] Figure 1 The surface SEM images of GPTMS-SiO2 coatings with different mass fractions clearly show that the coating surface is evenly distributed with micron-scale clusters of stacked nano-SiO2 particles, which evenly cover the surface. These micron-scale protrusions have densely distributed nano-scale papillary structures, and there are many pores between the papillae. The presence of pores provides conditions for the formation of an "air cushion" between the super-hydrophobic coating and water droplets, greatly reducing the actual contact area of ​​the liquid-solid interface, which is one of the reasons for giving the coating super-hydrophobic properties. As the concentration of the GPTMS-SiO2 dispersion increases, the degree of agglomeration of SiO2 nanoparticles also increases, resulting in the formation of a large number of irregular and highly rough porous structures on the surface.

[0037] The EDS element analysis results of SHP-GFRP-3# super hydrophobic coating are shown in Figure 2As shown in the figure, the main elements fluorine (F), oxygen (O), and silicon (Si) are evenly distributed. The reason is that the GPTMS modification improves the interaction between nano-SiO2 particles and FEVE, effectively inhibiting the large-scale agglomeration of nano-SiO2. The mass fractions of F, O, and Si are 19.64%, 34.31%, and 46.05%, respectively. The uniform distribution of F and Si elements on the coating surface not only provides a suitable rough structure for the coating, but also gives the coating surface extremely low surface energy.

[0038] At room temperature, the static contact angle and rolling angle of the composite coating surface change with the addition amount of super-hydrophobic nano-SiO2 particles. Figure 3 As shown. When the SiO2 concentration is low, the surface roughness formed is not enough to provide sufficient area to repel water droplets. However, when the SiO2 concentration is too high, excessive SiO2 is deposited on the coating surface, resulting in a decrease in the pores on the micro-nanostructure surface and a significant reduction in the air captured by the Cassie-Baxter structure, which in turn leads to a decrease in the contact angle. Only when the SiO2 addition amount is appropriate can SiO2 form a rough nanoscale microstructure on the composite coating surface and achieve a maximum contact angle of 156.1°.

[0039] In order to study the anti-icing performance of the composite coating, its icing delay ability was measured. The results are as follows: Figure 4 As shown. From the figure, two different wetting models can be clearly distinguished. The droplets on the uncoated surface show the Wenzel model hydrophilic state diagram (GFRP-0#), while the droplets on the composite coating surface show the Cassie-Baxter wetting state. The droplets on the GFRP-0# surface become turbid at 210s, indicating the beginning of freezing. During the freezing stage, no ice crystals appear inside the droplets, and the solidification front moves upward from the solid-liquid interface. At 358s, a "peach tip"-like protrusion forms on the top of the droplet, marking the end of freezing. The droplets on the SHP-GFRP-3# surface are still in liquid state before 2104s, then begin to freeze, and a "peach tip"-like protrusion appears at 2413s. The freezing delay time of the composite coating surface is significantly longer than that of the uncoated surface, and is positively correlated with the increase in contact angle. The reason is that during the cooling and freezing stages, the increase in surface contact angle and the corresponding increase in thermal resistance caused by trapped air reduce the heat transfer between the droplet and the surface, thereby significantly delaying the freezing time.

[0040] Depend on Figure 5It can be seen that, compared with the uncoated surface, the extension of the cooling time is the main contributor to the delay in the total ice formation time of the droplets on the composite coating surface. For the SHP-GFRP-3# surface with the largest contact angle, the cooling time accounts for 87.2% of the total ice formation delay time, which means that the large amount of air present on the surface of the micro-nano composite coating composed of hydrophobic FEVE and superhydrophobic GPTMS-SiO2 becomes a good thermal insulation layer, which can effectively prevent the droplets from freezing, thus delaying the time for the droplets to reach the nucleation temperature.

[0041] Figure 6 The test results of the ice adhesion force at different temperatures are shown. The results indicate that as the temperature increases, the ice adhesion force decreases. At -6°C, the adhesion forces of the five specimens are lower than those at -12°C. At the same temperature, the wettability and roughness of the surface will affect the ice adhesion strength on the material surface. The results show that the order of the adhesion force is SHP-GFRP-3# < HP-GFRP-2# < HP-GFRP-1# < HP-GFRP-4#, which means that the ice adhesion force decreases with the increase of the surface hydrophobicity. This law is satisfied within the ice formation contact area measured in the experiment. For example, when the ice column diameter increases from 10 mm to 20 mm, the contact area increases from 0.78 cm to 3.14 cm 2 。

[0042] From Figure 7 the static ice formation strength data, it can be seen that the increase in the adhesion area does not lead to obvious fluctuations in the adhesion strength, and its value is relatively stable. At an ambient temperature of -12°C, the average adhesion strength of the SHP-GFRP-3# surface is 97.6 kPa, and the reduction rate reaches 72.1% compared with 349.5 kPa of the GFRP-0# surface; while at -6°C, the average adhesion strength of the SHP-GFRP-3# surface is 87.16 kPa, and the reduction rate reaches 72.8% compared with 320.1 kPa of the GFRP-0# surface. From the contact angle data, it can be known that the droplets are in the Cassie-Baxter state on the composite coating surface. At this time, the air trapped in the nanostructure forms an air cushion. After the ice formation starts, the presence of air in the micro-nano structure reduces the effective contact area between the ice layer and the substrate, thus reducing the binding force. However, the uncoated surface is in the hydrophilic state of the Wenzel model. At this time, the actual contact area of the water droplet is larger than the projected area on the solid surface, and the ice layer formed by the water droplet shows a strong adhesion force on the surface and is more difficult to be removed.

[0043] Such as Figure 8As shown in the figure, WCA shows a downward trend with the increase of cycle number, but after 160 cycles of wear, the water contact angle of the surface of SHP-GFRP-3# dropped to 152.9°, which was only 3.2° lower than the initial contact angle of 156.1°, indicating that the surface of SHP-GFRP-3# maintained superhydrophobicity. The excellent wear resistance is due to the synergistic effect of two key factors. First, the FEVE primer coated on the substrate enhances the adhesion between the coating and the substrate. Second, the superhydrophobic SiO2 particles enter the semi-cured FEVE through self-sedimentation, ensuring the consistency of the internal structure and surface structure of the coating. Figure 2 Elemental analysis shows that the uniform distribution of fluorine, silicon and oxygen elements, and the addition of fluorine elements effectively reduce the surface energy of the exposed surface after coating wear. The uniform dispersion of super-hydrophobic SiO2 nanoparticles in the coating ensures that the nano-protrusion structure can be retained even in the case of surface wear. The existence of this structure maintains the low surface energy characteristics and roughness of the coating, ensuring the super-hydrophobicity of the coating after each wear cycle. Therefore, the self-sedimentation embedding technology of low surface energy nanoparticles plays a key role in maintaining the wear resistance of the coating.

[0044] Fig. 9 and Fig.10 The surface ice coverage at different air flow rates under -6℃ working conditions. Due to the influence of surface hydrophobicity, the ice coverage on the composite coating surface is thin and dispersed, while the ice coverage range and ice coverage density on the GFRP-0# surface are larger. Among them, the SHP-GFRP-3# surface has super hydrophobic properties, and water droplets are most likely to roll off, so the probability of freezing is the lowest, and the amount of ice on its surface is the least.

[0045] At different wind speeds, the change of ice mass over time is as follows: Fig.11 As shown. Under the conditions of 4m / s and 8m / s wind speeds, the final ice-covered masses of GFRP-0# and SHP-GFRP-3# are 8.28g and 10.19g, 3.58g and 4.63g respectively. As can be seen from the figure, the increase in wind speed leads to an increase in the amount of ice on the surface. High wind speed brings more cooling water droplets, accelerates the heat exchange between the droplets and the environment, and increases the kinetic energy of the droplets, expands the impact area, and makes the ice area wider, thereby increasing the amount of ice.

[0046] The ice mass reduction rate is an important indicator to measure the anti-icing performance of different coatings. Fig.12As shown in the figure, from the ice mass reduction rate curves of the composite coating surface at different times, it can be seen that the ice mass reduction rate of the super-hydrophobic SHP-GFRP-3# surface under v = 4m / s and v = 8m / s conditions decreased from 68.91% and 69.43% at 5 minutes to 56.78% and 54.58% at 30 minutes, respectively. This is because in the initial period of ice formation, the droplet residence time on the super-hydrophobic surface is short and the ice coating speed is slow. After part of the position is covered by ice, the ice coating speed increases, causing the ice mass reduction rate of the surface to gradually decrease with time.

Claims

1. A method for preparing a nano-silicon dioxide / fluorocarbon resin durable super-hydrophobic composite coating, characterized in that: The following steps are involved: (1) dispersing nano-silica particles in anhydrous butanol and subjecting them to ultrasonic treatment; mixing γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent with water, stirring to fully hydrolyze, and cooling to room temperature; mixing the silane coupling agent / water mixed solution and the nano-silica / butanol mixed solution evenly, and subjecting them to magnetic stirring in a water bath to obtain γ-GPTMS-modified SiO2 nanoparticles; (2) preparing a main agent solution with a fluorocarbon resin and an isocyanate, preparing a diluent with butyl acetate and propylene glycol methacrylate, mixing the main agent solution and the diluent, stirring them magnetically in a beaker, vacuuming and degassing to obtain a composite coating film-forming material, spraying the composite coating film-forming material on the surface of a glass fiber reinforced epoxy resin board, and pre-curing the composite coating film-forming material to form a bottom bonding layer; (3) A certain amount of γ-GPTMS-modified SiO2 nanoparticles was mixed with butanol to obtain a surface layer solution, which was evenly stirred and ultrasonically dispersed, and then evenly sprayed on the surface of the underlying bonding layer by a spray gun to form a surface layer. After curing, a nano-silica / fluorocarbon resin durable super-hydrophobic composite coating was obtained.

2. The method according to claim 1, characterized in that In step (1), the mass content of the nano-silicon dioxide particles in anhydrous butanol is 0.004-0.03 g / mL.

3. The method according to claim 1, characterized in that In step (1), the γ-(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent and water are mixed in a ratio of 1:1-1:

5.

4. The method according to claim 1, characterized in that In step (1), the mixture is stirred magnetically in a water bath at 50-70° C. for 0.5-3 h.

5. The method according to claim 1, characterized in that In step (2), the mass ratio of fluorocarbon resin to isocyanate in the main solvent is 20:1-10.

6. The method according to claim 1, characterized in that In step (2), the mass concentration of butyl acetate in the diluent is 50-70%.

7. The method according to claim 1, characterized in that In step (2), the main agent solution and the diluent are mixed in a mass ratio of 10:8-10:

1.

8. The method according to claim 1, characterized in that In step (2), pre-curing is carried out at 30-70°C.

9. The method according to claim 1, characterized in that: In step (3), the concentration of SiO2 in the surface layer solution is 2-30%.

10. Application of the method according to any one of claims 1 to 9 on wind turbine blades.

Citation Information

Patent Citations

  • Composite material, preparation method and application thereof

    CN109929285A

  • Preparation method of silicon dioxide nanoparticle / organic resin composite super-hydrophobic coating

    CN113956755A

  • Preparation method of super-hydrophobic composite coating capable of preventing icing for long time and method for recovering anti-icing property of super-hydrophobic composite coating

    CN115304965A

  • Anti-icing hydrophobic coating as well as preparation method and application thereof

    CN116836593A

  • Superhydrophobic coatings and methods of preparation

    WO2013042052A1

Cited By

  • Preparation method of SiO2-based double-covalent network super-hydrophobic composite coating

    CN119799044A

  • Sensor probe and fiber bragg grating wind speed sensor

    CN120629630A

  • Wind power solid waste fiber polymerization modification method

    CN120794406A

  • A method for modifying wind power solid waste fibers by polymerization

    CN120794406B

  • Composite coating based on waste silicate building glass micropowder and preparation method thereof

    CN120988582A